Anomalous mechanical strengths and shear deformation paths of Al2O3 polymorphs with high ionicity. Issue 16 (3rd February 2016) - Zhang, Z.; Fu, Z. H.; Zhang, R. F.; Legut, D.; Guo, H. B.
Abstract : Alumina (Al2 O3 ) formed by selective oxidization provides an effective way to protect aluminide alloys against corrosion for sustainable applications. Abstract : Alumina (Al2 O3 ) formed by selective oxidization provides an effective way to protect aluminide alloys against corrosion for sustainable applications. Despite a broad interest and investigations on Al2 O3 polymorphs such as α-Al2 O3 and θ-Al2 O3, their intrinsic mechanical strengths and atomic deformation mechanisms are not yet fully understood. In this research, density functional theory is used to show that the calculated shear moduli and mechanical strengths of θ-Al2 O3 are substantially lower than those of α-Al2 O3, and this explains why θ-Al2 O3 is much weaker than α-Al2 O3 . An analysis of shear deformation paths and electronic structure indicates that the longest Al–O ionic bonds are responsible for the lattice instability of both polymorphs during shear, showing they have different anisotropic features. This study gives a novel view on the failure of thermally grown α-Al2 O3 and θ-Al2 O3, and it should help to improve the performance of thermal barrier coatings.